PARTICULAR QUALITIES OF RECONCILIATION PROCEDURES IN THE INTERETHNIC CONFLICT - Dyachuk, Марианна Ивановна; Kazbayeva , Асель Габиденовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The authors devote their work studying the problems of resolving conflicts and disputes in the field of interethnic relations, revealing the content and functional components of this category. This article examines the causes of local ethnic conflicts. Factors, hindering the harmonization of interethnic relations. Principles of action to neutralize the confrontational aspirations of participants in interethnic conflicts. The work represents approaches to the definition of ethnic conflict and its typology, reflects the specificity and commonality of ethnic disputes and conflicts relating to disputes and conflicts of other generally recognized types. The authors compared reconciliation procedures. The concept of a settlement agreement as a reconciliation procedure, as well as the definition of mediation are presented and their stages are considered. In the course of studying this topic, the subject of the research was the norms of national legislation regulating the possibility of appealing to reconciliation procedures, and the emerging judicial practice, norms of substantive legislation, theoretical developments about reconciliation procedures, general patterns of formation, development and implementation of reconciliation procedures; as well as the experience of foreign countries in the field of their application in resolving interethnic disputes and conflicts through the use of a mediation approach in a multicultural society. These provisions can be used for further theoretical research of the institution of reconciliation procedures and to find application in scientific and educational activities.